An extracellular matrix protein promotes anillin-dependent processes in the Caenorhabditis elegans germline - Lan, Hongxia (Life Sci Alliance, 2019)
Cell division requires constriction of an actomyosin ring to segregate the genetic material equally into two daughter cells. The spatial and temporal regulation of the contractile ring at the division plane primarily depends on intracellular signals mediated by the centralspindlin complex and astral microtubules. Although much investigative work has elucidated intracellular factors and mechanisms controlling this process, the extracellular regulation of cytokinesis remains unclear. Thus far, the extracellular matrix protein Hemicentin (HIM-4) has been proposed to be required for cleavage furrow stabilization. The underlying molecular mechanism, however, has remained largely unknown. Here, we show that HIM-4 and anillin (ANI-1) genetically act in the same pathway to maintain the rachis bridge stability in the germline. Our FRAP experiments further reveal that HIM-4 restricts the motility of ANI-1. In addition, we demonstrate that HIM-4 is recruited to the cleavage site in dividing germ cells and promotes the proper ingression of the cleavage membrane. Collectively, we propose that HIM-4 is an extracellular factor that regulates ANI-1 for germ cell membrane stabilization and contractile ring formation in Caenorhabditis elegans germline cells.